Impact of lipid-lowering therapy on glycemic control and the risk for new-onset diabetes mellitus - Constantine E Kosmas; Delia Silverio; Andreas Sourlas; Frank Garcia; Peter D Montan; Eliscer Guzman (BioExcel Publishing Ltd, 2018)
Lipid-lowering therapy is used very commonly nowadays not only for the optimization of the lipid profile but also to reduce cardiovascular risk. However, some studies have linked the use of certain lipid-lowering agents with an increased risk for impaired glycemic control and new-onset diabetes mellitus, a condition well established as an important risk factor for cardiovascular disease. On the other hand, some other lipidlowering agents have been shown to have a beneficial effect on glucose metabolism. Profound knowledge of these differences would enable the clinician to choose the right lipid-lowering medication for each individual patient, so that the benefits would outweigh the risk of side effects. This review aims to present and discuss the clinical and scientific data pertaining to the impact of lipid-lowering therapy on glycemic control and the risk for new-onset diabetes mellitus.